The implication of HRM practices towards employee retention in MARA Headquarter / Nurathirah Latif and Siti Aisyah Bahrudin - Latif, Nurathirah; Bahrudin, Siti Aisyah (Faculty of Business and Management, 2016)
Employee retention refers to the ability of an organization to retain its employees. The purpose of this study is to investigate the relationship between Human Resource Management Practices (HRM) in MARA Headquarter. In this study only 137 respondents which are employees at Human Resource Department selected using simple random sampling. The objectives of this study aim to investigate the level of employee retention among MARA Headquarter staff, to examine the dominant factor that can contribute to employee retention and to identify the relationship between HRM practices and employee retention. Eventually, this research discovered that most of the respondents were age between 26 - 35 years, female, married, permanent staff, Degree/Diploma education and 6-10 years working there. Besides that, this study is a quantitative research study whereby the findings of the study were analysed by using the Statistical Package for the Social Science (SPSS) version 20.0. The data collected in this study is analysed by using frequency, descriptive analysis, reliability, Pearson’s correlation analysis and multiple regressions in order to achieved the research objectives. After the data have been analysed, the result showed that, there is a significance correlation between the employee empowerment factors with the employee retention. This study also said to be beneficial to organization in order to increase the employee retention. At the end of this research, some of the recommendations are also having been discussed.